Successful Removal of a Posterior Cardiac Lipoma by Transection of the Ascending Aorta and Main Pulmonary Artery. (17th August 2022) - Watanabe, Saeki; Ichihara, Yuki; Morita, Kozo; Saito, Satoshi; Niinami, Hiroshi
Abstract : Primary cardiac tumors are unusual, whereas lipomas are particularly rare. We successfully removed a very large posterior cardiac lipoma by transecting the ascending aorta and main pulmonary artery. Transecting both the ascending aorta and the main pulmonary artery facilitated surgical exposure and complete removal of the posterior cardiac lipoma.